Histological and histochemical changes in the peripheral organs of the immune system of dogs in cases of isoniazid poisoning - G. I. Kotsyumbas; N. P. Vretsona (Regulatory Mechanisms in Biosystems, 2021)
Most publications on isoniazid poisoning in dogs are devoted to clinical diagnostics, treatment, and prevention of the disease. Histological and histochemical changes are not fully described, though they are important in assessing the toxic effects of isoniazid. Isoniazid is used to treat tuberculosis in humans. Dogs are hypersensitive to this drug. The article highlights the results of macroscopic, histological, and histochemical studies of the dogs’ lymph nodes and spleen in cases of isoniazid poisoning. A pathological examination of 19 corpses of dogs of different ages was performed, during which isoniazid poisoning was posthumously diagnosed, based on anamnesis, clinical signs, pathological autopsy, histological, and histochemical examination. Samples of lymph nodes and spleen were fixed in a 10% aqueous neutral formalin solution, Carnoy’s solution, and Bouin’s fixative. Histoсuts were prepared using a sled microtome and stained with hematoxylin and eosin. Staining was also performed according to the techniques suggested by McManus, Brachet, and Perls. The pathomorphological changes in lymph nodes and spleen were characterized by disorganization of vascular walls and connective tissue fibers of the stroma, dilatation of veins, their overflow with hemolyzed blood, and, in cases of the long clinical course, thrombosis of small vessels. Intravascular hemolysis of erythrocytes resulted in an excessive formation of hemosiderin. Histochemically, the spleen and lymph nodes showed a significant increase in the number of hemosiderophages in the spleen’s red and white pulp and the lymph nodes’ central sinuses and pulp cords. In the spleen, mucoid swelling and necrobiotic changes in the wall structures of the arterioles and arteries progressed with a narrowing of their lumen in dogs suffering from the long clinical course. Increased permeability of the microcirculatory tract vessels of the spleen and lymph nodes, transudate formation, and the destructive changes in the reticular skeleton accompanied hemodynamic violations. A sharp change in blood rheology caused the violation of trophism and metabolism in the immune system. Lymphoid elements of the lymph nodes and white pulp of the spleen were in a state of karyorrhexis and karyolysis. The morphological study of the immune system’s peripheral organs suggests that dogs poisoned by isoniazid demonstrate hemodynamic disorders, changes in the physicochemical properties of blood (hemolysis of erythrocytes and thrombosis). This is the basis of trophic disorders, metabolic malfunctions, and the development of dystrophic processes in all structural elements of the spleen and lymph nodes.